Scalable trusted online dissemination of JPEG2000 images - DENG, Robert H. (Institutional Knowledge at Singapore Management University, 2005)
An important aspect of JPEG2000 is its “compress once, decompress many ways” property [1], i.e., it allows users with different preferences, privileges or capabilities to extract various sub-images all from a single compressed image code-stream. In this paper, we present a flexible and scalable scheme to authenticate JPEG2000 images disseminated by a untrusted third-party server over open networks. The proposed scheme is fully compatible with JPEG2000 and possesses a “sign once, verify many ways” property, i.e., it allows users to verify the authenticity and integrity of different sub-images extracted from a single compressed code-stream protected with a single digital signature. Furthermore, the use of aggregated digital signatures reduces both computation and communication overhead on the user side for batch image authentication.